Serum amyloid A1 exacerbates hepatic steatosis via TLR4-mediated NF-κB signaling pathway - Bin Jiang; Dongdong Wang; Yunfu Hu; Wenxuan Li; Fengjiang Liu; Xudong Zhu; Xiaoyu Li; Hanwen Zhang; Hui Bai; Qing Yang; Xiuna Yang; Jingjing Ben; et al. (Elsevier, 2022)
Objective: Chronic inflammatory response plays a prominent role in obesity-related nonalcoholic fatty liver disease (NAFLD). However, the intrahepatic triggering mechanism of inflammation remains obscure. This study aimed to elucidate the role of serum amyloid A1 (SAA1), an acute-phase response protein, in the obesity-induced hepatic inflammation and NAFLD. Methods: Male mice were fed a high fat diet (HFD) for 16 weeks, and insulin resistance, hepatic steatosis, and inflammation in mice were monitored. Murine SAA1/2 was genetically manipulated to investigate the role of SAA1 in NAFLD. Results: We found that SAA1 was increased in the NAFLD liver in both humans and mice. Knockout of SAA1/2 or knockdown of hepatic SAA1/2 promoted energy expenditure and alleviated HFD-induced metabolic disorder, hepatic steatosis, and inflammation. Endogenous overexpression of SAA1 in hepatocytes by adeno-associated virus 8 (AAV8) transfection aggravated overnutrition-associated gain of body weight, insulin resistance, hepatic lipid accumulation, and liver injury, which were markedly alleviated by knockout of murine toll-like receptor 4 (TLR4). Mechanistically, SAA1 directly bound with TLR4/myeloid differentiation 2 (MD2) to induce TLR4 internalization, leading to the activation of nuclear factor (NF)-κB signaling and production of both SAA1 and other inflammatory cytokines, including interleukin (IL)-6 and C-C chemokine ligand (CCL2) in hepatocytes. Administration of HFD mice with an AAV8-shRNA-SAA1/2 showed a therapeutic effect on hepatic inflammation and NAFLD progression. Conclusions: These results demonstrate that SAA1 triggers hepatic steatosis and intrahepatic inflammatory response by forming a SAA1/TLR4/NF-κB/SAA1 feedforward regulatory circuit, which, in turn, leads to NAFLD progression. SAA1 may act as a potential target for the disease intervention.